Olfactory neuroblastoma is a peripheral primitive neuroectodermal tumor related to Ewing sarcoma. - Sorensen, P H (1996)
Olfactory neuroblastoma (ONB) is a malignant tumor of the nasal mucosa whose histogenesis is unclear. A relationship to neuroblastoma (NB), a pediatric tumor of the sympathetic nervous system, is based on morphologic similarities and the expression of similar neural antigens. However, the clinical presentation of ONB differs from that of NB, and MYCN amplification characteristic of NB is not observed. We have therefore examined the relationship of this malignancy to other classes of neural tumors. In previous studies, two ONB cell lines demonstrated cytogenetic features and patterns of protooncogene expression suggestive of a relationship to the Ewing sarcoma family of childhood peripheral primitive neuroectodermal tumors (pPNETs). The pPNETs show t(11;22)(q24;q12) or t(21;22)(q22;q12) chromosomal translocations fusing the EWS gene from 22q12 with either the FL11 gene on 11q24 or the ERG gene on 21q22. We therefore analyzed ONBs for the presence of pPNET-associated gene fusions. Both cell lines showed rearrangement of the EWS gene, and fluorescence in situ hybridization (FISH) of each case demonstrated fusion of EWS and FL11 genomic sequences. Moreover, both lines expressed EWS/FL11 fusion transcripts with in-frame junctions between exon 7 of EWS and exon 6 of FL11 as described for pPNETs. We identified similar gene fusions in four of six primary ONB cases. None of the cases expressed tyrosine hydroxylase, a catecholamine biosynthetic enzyme widely expressed in NB. Our studies indicate that ONB is not a NB but is a member of the pPNET family.